Measurement of fruit color-heterogeneity index and their relation to Jatropha curcas L., oil in Colombia (2017)
Jatropha curcas L. is a wild species in the domestication process with an oil and biofuel potential use. The evolutionary-adaptive processes have conferred a reproductive mechanism based on protogyny-geitonogamy, achieving a floral asynchrony addressed to ensure the outcrossing and survival in extreme climate and soil conditions. In the wild, this plant performs a fruit heterogeneity, an unattractive attribute for harvest timing. Therefore, this research aimed to determine the number of harvest, yield and proportion, and physiological states of fruit maturity with the maximum oil quantity and quality. A randomized complete block factorial arrangement of treatments design was performed. The varieties and stages of fruit ripeness, were the factors. A relation of 19: 31: 36: 14 with fruits pericarp colors: green: yellow: yellow-brown: brown, was obtained. The best harvest timing was during the yellow-brown state, which represented the highest oil content associated with high oleic acid and linoleic contents. Nevertheless, for a fruit harvest timing, the use of the epicarp color index is recommended. These results suggest the floral asynchrony breeding traits, requires the ensuring of the fruit homogeneity for mechanical or manual harvesting.